2020
DOI: 10.1101/2020.06.05.135780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-Translational Modifications Soften Vimentin Intermediate Filaments

Abstract: The mechanical properties of biological cells are determined by the cytoskeleton, a composite biopolymer network consisting of microtubules, actin filaments and intermediate filaments (IFs). By differential expression of the cytoskeletal proteins, modulation of the network architecture and the interactions between the filaments, cell mechanics may be adapted to varying requirements on the cell. Here, we focus on the intermediate filament protein vimentin and introduce post-translational modifications as an add… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, because IF assembly and disassembly are regulated by phosphorylation and other posttranslational modifications (18), it will be interesting to investigate whether these modifications alter the axial repeat of IFs, reflecting changes in their structural organization. In vitro work already showed that phosphorylation of vimentin by adenosine 3′,5′monophosphate-dependent protein kinase A soften the filaments (44). Moreover, it would be also relevant to determine whether other IF types, such as keratins or neurofilaments, also have an axial repeat and also unfold their  helices cooperatively during filament stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because IF assembly and disassembly are regulated by phosphorylation and other posttranslational modifications (18), it will be interesting to investigate whether these modifications alter the axial repeat of IFs, reflecting changes in their structural organization. In vitro work already showed that phosphorylation of vimentin by adenosine 3′,5′monophosphate-dependent protein kinase A soften the filaments (44). Moreover, it would be also relevant to determine whether other IF types, such as keratins or neurofilaments, also have an axial repeat and also unfold their  helices cooperatively during filament stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because IF assembly and disassembly are regulated by phosphorylation and other post-translational modifications (18), it will be interesting to investigate whether these modifications alter the axial repeat of IFs, reflecting changes in their structural organization. In vitro work already showed that phosphorylation of vimentin by cAMP-dependent protein kinase A soften the filaments (44).…”
Section: Discussionmentioning
confidence: 99%
“…The Nterminus of vimentin is targeted by several protein kinases that phosphorylate neutral serine residues to bestow a negative charge, and protein arginine deiminases that convert positively-charged arginine to neutral citrulline [10]. These alterations of charge can lead to filament disassembly, and at lower extents of alteration can decrease the stiffness of the filament [33].…”
Section: Molecular Structure Of Vimentin Filamentsmentioning
confidence: 99%